Pengembangan dan Uji Efektivitas Model Strategi Pelatih Berbasis Motivasi pada Atlet Futsal Usia 13 Tahun - Abdurrajab Arif; Muchamad Ishak; Bangbang Syamsudar (Universitas Hamzanwadi, 2026)
Motivation among young athletes is a crucial factor in the sustainability of high-performance futsal development; however, the motivational strategies employed by coaches at Indonesian futsal academies remain intuitive and unstructured. This study aims to develop and test the initial effectiveness of a motivation-based coaching strategy model to enhance the motivation of 13-year-old futsal athletes. The study employs a Research and Development (R&D) approach, which includes needs analysis, model design, expert validation, pilot testing, and revision. The effectiveness test used a one-group pretest-posttest quasi-experimental design involving 14 athletes. The instrument was a motivation questionnaire based on Self-Determination Theory (SDT) that measured intrinsic, extrinsic, and amotivational motivation. Expert validation results indicated the model was highly feasible (average score of 3.62). The effectiveness test showed a significant increase in intrinsic motivation (p < 0.001; d = 1.63) and extrinsic motivation (p = 0.002; d = 0.89), as well as a significant decrease in amotivation (p < 0.001; d = 1.32). The conclusion of this study is that the motivation-based coaching strategy model has been proven effective in improving the quality of motivation among 13-year-old futsal athletes. This model is recommended as a practical guide for coaches in creating a training environment that is supportive, participatory, and oriented toward the development of long-term motivation.